2017
DOI: 10.3390/catal7110313
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive Hybrid Film Photocatalyst of Polyethersulfone-ZnO for the Degradation of Methyl Orange Dye: Kinetic Study and Operational Parameters

Abstract: Abstract:A facile and effective technique to immobilize photocatalyst nanoparticles by incorporating zinc oxide (ZnO) into polyethersulfone polymeric films by means of a phase inversion technique is reported. The degradation study of methyl orange (MO) dye was performed using a series of ZnO-embedded polymer hybrid systems. The photoactivity of the films increased in parallel with increased ZnO loading up to 17 wt%. The photodegradation process followed a pseudo first-order kinetics with an achievement of almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The decomposition of the dye chromogen resulted in solution decolorization, reflecting a decrease in the dye absorbance ( Figure 3). The results also showed that the photocatalytic degradation activity of ZnO-coated textile substrates increased with increasing surface porosity, roughness, specific surface area, and hydrophilicity [12,21]. These factors facilitate the adsorption of the dye onto the ZnO Ps and enhance the formation of ROS.…”
Section: Photocatalytic Self-cleaning Propertiesmentioning
confidence: 86%
See 3 more Smart Citations
“…The decomposition of the dye chromogen resulted in solution decolorization, reflecting a decrease in the dye absorbance ( Figure 3). The results also showed that the photocatalytic degradation activity of ZnO-coated textile substrates increased with increasing surface porosity, roughness, specific surface area, and hydrophilicity [12,21]. These factors facilitate the adsorption of the dye onto the ZnO Ps and enhance the formation of ROS.…”
Section: Photocatalytic Self-cleaning Propertiesmentioning
confidence: 86%
“…ZnO-coated textile substrates have previously been used for the solar-driven photodegradation process of toxic organic compounds in water and air. To this end, ZnO-coated polyester [21,103,104,119] or cotton [12] substrates were immersed in different dye solutions, such as methylene blue, methyl orange, C.I. Acid Blue 9, C.I.…”
Section: Photocatalytic Self-cleaning Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the photocatalytic recital of 4% Zr:SnO 2 nanostructured PCs is intensely upgraded owing to the synergistic things, which embrace the sturdier light fascination, the calmer light excitation, the improved charge carrier's departure, further effectual of oxygen adsorption and additional photoactivity sites. In addition, the photocatalytic presentations of the as-obtained 4% of Zr:SnO 2 PCs were associated with recently testified PCs by different semiconductors metal oxides/metal and auxiliary nanocomposites are deliberated in Table 1 (Xin et al 2012;Shivaraju et al 2017;Raliya et al 2017;Hir et al 2017;Mbuli et al 2019). Hereafter it has comprehended that the Zr:SnO 2 PCs have upgraded catalytic proficiency analogized with further comprehensive photocatalytic materials.…”
Section: Photocatalytic Mechanisms Of Obtained Photocatalystmentioning
confidence: 99%